Sosialisasi Pembuatan Yoghurt Kacang Tanah sebagai Pemberdayaan Masyarakat untuk Peningkatan Ekonomi Di Desa Landungsari Kecamatan Dau Kabupaten Malang - Ma'unatin, Anik; Jannah, Akyunul; Sulhan, Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The increase in public awareness of health during the Covid 19 pandemic was accompanied by an increasing need for functional food including probiotic drinks. One of the efforts to diversify yogurt is by using peanuts as a substitute for cow's milk. The production of peanuts which is quite a lot in Malang allows it to be processed into Plant-based yogurt. As an effort to increase independence in the field of entrepreneurship in peanut-producing area in Desa Landungsari Kecamatan Dau Malang, it was necessary to provide socialization on making peanut yogurt and business development through the digital economy by the program team serving Qaryah Thayyibah UIN Maulana Maliki Ibrahim Malang.